Double-BODIPY-based organic solar cell small molecule donor material and preparation method and application thereof
By introducing triphenylline or carbazolyl into BODIPY derivatives, designing and synthesizing bi-BODIPY-based small-molecular donor materials ZMH-3 and ZMH-4, the problem of low efficiency of existing small-molecular organic solar cells is solved, and the realization of the realization of low efficiency of existing small-molecular organic solar cells is achieved. Efficient photoelectric conversion efficiency.
Patent Information
- Application Number
- CN202411463167.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The power conversion efficiency of existing small molecule organic solar cells is low, making it difficult to design and synthesize efficient small molecule donor materials.
The pentafluorophenyl BODIPY derivative using strong electron withdrawal at the meso position is connected by covalent bonding, and triphenyl (TPA) or carbazole (CZ) groups are introduced as electron donors at the 3rd and 5th positions of the BODIPY parent, respectively, through the molecular structure. Modification regulates molecular spectral absorption, energy level distribution and crystallinity to prepare the dual BODIPY-based small-molecular donor materials ZMH-3 and ZMH-4.
By using ZMH-3 and ZMH-4 and non-fullerene electron acceptor ITIC as active layer materials, the photoelectric conversion efficiency of organic solar cells can reach up to 12.26%, with good application prospects.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the fields of organic compound synthesis, organic solar energy and fine chemical technology, and specifically relates to the preparation and application of a BODIPY-based solar cell small molecule donor material. Background Art
[0002] The exhaustion of fossil energy and the severe domestic and international situation have made the energy crisis more serious. The over-exploitation of traditional fossil energy and the emission of secondary organisms in the use have also caused serious environmental and social problems. The development of clean energy has become increasingly important. Among them, organic solar cells (OSCs) based on heterojunction (BHJ) active layers (mixtures of organic semiconductor donor and acceptor materials) have attracted the attention of many researchers due to their potential advantages. First, the types and sources of OSCs are very wide, and they do not contain any rare elements; second, the structural tunability of this type of material is very large, and functional molecules with target band gaps and absorption ranges can be obtained by optimizing and adjusting the structure. For example, compounds that absorb in the visible light region can be used in the field of indoor soft light; third, OSCs can be processed by solution method and can be mass-produced by roll-to-roll printing technology, which is low in cost and conducive to large-scale commercialization; finally, due to its characteristics of no pollution, no noise, low cost, light weight, and the ability to prepare flexible devices, it has great application prospects in future flexible wearable devices. Therefore, more and more researchers are engaged in research in this field.
[0003] The core of organic solar cells is organic semiconductor materials with photosensitive properties. Organic materials have the characteristics of light weight, simple preparation, translucency, and can be made into flexible devices, showing great development potential in the field of photovoltaics. However, polymers are difficult to control and have poor reproducibility, which is not only not conducive to the analysis of their structure, but also different degrees of polymerization will affect the performance of the device, resulting in differences in the performance of solar cells with the degree of polymerization of the polymer. Compared with polymer materials, small molecule organic materials have the advantages of solubility, simple synthesis and purification, easy modification of molecular structure and no batch variation. However, the small area power conversion efficiency (PCE) of small molecule solar cells (SMDs) lags far behind that of polymers as donors. At present, it is still a great challenge to design and synthesize small molecule donors with high PCE. Therefore, it is of great scientific significance to rationally design and optimize the molecular configuration and construct efficient small molecule donors that match these excellent acceptors.
[0004] As an important class of multifunctional fluorophores, boron dipyrrole (BODIPY) dyes have many excellent optical properties, such as relatively high molar extinction coefficient and fluorescence quantum yield, good photochemical and thermal stability, and low optical band gap. In addition, BODIPY derivatives are easy to synthesize, and their photophysical and electrochemical properties can be rationally adjusted by appropriate synthetic modification of the BODIPY core and introduction of appropriate electron donors and electron acceptors. Therefore, the superior photophysical and electrochemical properties of BODIPY and its superior modifiability make it have broad application prospects in the field of organic solar cells.
[0005] The present invention relates to the preparation and application of small molecule donor materials for organic solar cells. Pentafluorophenyl BODIPY derivatives with strong electron withdrawal at the meso position are connected by covalent bonds, and triphenylamine (TPA) or carbazole (CZ) groups are introduced at the 3rd and 5th positions of the BODIPY matrix as electron donors. The molecular spectral absorption, energy level distribution and molecular crystallinity are effectively adjusted through molecular structure modification, thereby improving device performance and providing new ideas for designing and synthesizing new SMDs. The small molecule donors ZMH-3 and ZMH-4 and non-fullerene electron acceptor ITIC are used as active layer materials in organic solar cells to obtain good results, and the photoelectric conversion efficiency can reach up to 12.26%, which has good application prospects in the field of organic solar cells. Summary of the invention
[0006] Purpose of the invention: In view of the deficiencies in the prior art, the purpose of the present invention is to prepare a class of small molecule donor materials for double BODIPY-based organic solar cells and their applications.
[0007] Technical solution: In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0008] The present invention discloses a type of double BODIPY-based organic solar cell small molecule donor material preparation and application, characterized in that the compound has the structural formula shown in formula ZMH-3 and ZMH-4:
[0009]
[0010] The method for preparing the small molecule donor material for an organic solar cell of the present invention comprises the following steps:
[0011] 1) Under nitrogen protection, the BODIPY monomer derivative (I) is dissolved in dry dichloromethane, and a nitromethane solution of ferric chloride is added dropwise at -78°C. After the addition is completed, the mixture is reacted for half an hour, and the temperature is naturally raised to room temperature. The reaction mixture is diluted with dichloromethane and washed with water. The organic layer is dried over anhydrous sodium sulfate, the solvent is removed by distillation under reduced pressure, and then separated and purified by silica gel column chromatography, with the eluent being dichloromethane-petroleum ether (v:v=1:1), to obtain compound (II);
[0012] 2) Under anhydrous conditions, compound (II) and 4-(N,N-diphenylamino)benzaldehyde and 9-butyl-9H-carbazole-3-carboxaldehyde are placed in a 100 mL double-necked reaction bottle, freshly dried p-toluenesulfonic acid is added, and then 10 mL of anhydrous toluene is added to dissolve, and 0.2 mL of piperidine is added as a catalyst, and heated to reflux for 4 to 6 hours. After the reaction is completed, the mixture is cooled to room temperature, diluted with dichloromethane, washed with water, and the organic layer is dried over anhydrous sodium sulfate. The solvent is removed by distillation under reduced pressure, and then separated and purified by silica gel column chromatography, and the eluent is dichloromethane-petroleum ether (v:v=1:1), to obtain small molecule donor materials ZMH-3 and ZMH-4. The specific chemical reaction formula is as follows:
[0013]
[0014] In the above step 1), the molar ratio of BODIPY monomer derivative (I) to ferric chloride is 1:3;
[0015] In the above step 2), the molar ratio of compound (II), p-toluenesulfonic acid and 4-(N,N-diphenylamino)benzaldehyde is 1:1:5.0, the molar ratio of compound (II), p-toluenesulfonic acid and 9-butyl-9H-carbazole-3-carbaldehyde is 1:1:5.0, and the volume and molar ratio of toluene, piperidine and compound (I) is 50 mL:1 mL:1 mmol;
[0016] The application of the small molecule donor in the organic solar cell of the present invention comprises the following steps:
[0017] (1) The ITO glass was ultrasonically cleaned with detergent, deionized water, acetone, and isopropanol, and then vacuum dried;
[0018] (2) Spin coating PEDOT:PSS on the ITO glass at a spin coating speed of 2500 rpm / min to prepare a hole transport layer with a thickness of 35 to 40 nm;
[0019] (3) dissolving the electron donor and the electron acceptor materials of ZMH-3:ITIC and ZMH-4:ITIC in a certain mass ratio in chloroform solvent at a concentration of 16 mg / mL, and spin-coating them on the hole PEDOT:PSS transport layer at room temperature and nitrogen atmosphere at a spin-coating speed of 2500 rpm / min for 60 s to form a bulk heterojunction film; and then treating them by solvent vapor annealing, exposing them to tetrahydrofuran vapor for 40 s annealing;
[0020] (4) dissolving PFN in methanol solvent and spin coating it on the top of the active layer at a spin coating speed of 3000 rpm / min for 1 min to form an electron transport layer;
[0021] (5) Under vacuum conditions, metallic aluminum (Al) is thermally evaporated and deposited on top of the PFN electron transport layer.
[0022] The organic solar cell described in the present invention has a structure of transparent conductive substrate (ITO glass), hole transport layer (poly (3, 4-ethylenedioxythiophene) (PEDOT): poly (styrene sulfonic acid) (PSS)), organic active layer, electron transport layer (polyfluorene derivative (PFN)), and metal electrode (Al) from bottom to top. The organic active layer is a bulk heterojunction ZMH-3:ITIC or ZMH-4:ITIC of a donor and an acceptor;
[0023] The molecular structures of the small molecule donors ZMH-3 and ZMH-4 and the non-fullerene condensed ring electron acceptor material ITIC in the organic active layer of the present invention are shown below:
[0024]
[0025] Beneficial effects of the present invention
[0026] Compared with the prior art, the present invention provides a class of biBODIPY-based organic solar cell small molecule donor materials and a preparation method and application thereof, which have the following advantages: (1) the donor reaction steps of this class of small molecule solar cells are simple, the reaction conditions are mild, the selectivity is good, and the synthesis cost is low; (2) the two donor molecules ZMH-3 and ZMH-4 have long absorption wavelengths, wide absorption ranges, narrow molecular energy levels, and high carrier performance, and are complementary to the absorption spectrum of the acceptor material ITIC, which can broaden the light absorption range of the entire system, thereby facilitating the improvement of the short-circuit current (Jsc) and photoelectric conversion performance of the device; (3) they can be used as electron donor materials to prepare organic small molecule organic solar cell devices, and their photoelectric conversion efficiency can reach up to 12.26%, which makes them have good application prospects in solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is the electron absorption spectrum of the donor material ZMH-3, ZMH-4 and the acceptor material ITIC film, where the abscissa is the wavelength (wavelength), in nm, and the ordinate is the absorbance;
[0028] Figure 2The fluorescence emission spectra of the donor materials ZMH-3, ZMH-4 and their thin films blended with the acceptor material ITIC, where the abscissa is the wavelength (nm), and the ordinate is the emission intensity;
[0029] Figure 3 The energy level diagram of the donor materials ZMH-3, ZMH-4 and the acceptor material ITIC in the organic solar cell prepared by the present invention, the ordinate is the energy level (Energy level), the unit is eV;
[0030] Figure 4 In the application of the small molecule donor of the present invention in organic solar cells, under the preferred conditions, the device current (J) of the solar cell based on (a) ZMH-3: ITIC and (b) ZMH-4: ITIC sc )-Voltage(V oc )picture. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with the specific drawings.
[0032] use 1 H-NMR and MALDI-TOF-MS spectra characterized and confirmed that it has a donor structure for a small molecule solar cell. The instruments used for detection are: Bruker ARX400 nuclear magnetic resonance instrument, Bruker ARX600 nuclear magnetic resonance instrument (both use deuterated chloroform as solvent), Shimadzu UV-3100 ultraviolet-visible spectrophotometer (scanning range 300-900nm, optical path slit 2nm), and fluorescence spectrum tested using American Amico Bowman Series 2 Luminescence Spectrometer. The device photoelectric conversion efficiency was measured using Keithley 2400 source meter (AM1.5G, 100mW / cm 2 )test.
[0033] Example 1
[0034] Preparation of compound (II)
[0035] Under nitrogen protection, the monomer BODIPY derivative (I) (134 mg, 0.4 mmol) was dissolved in dry dichloromethane (100 mL), and a nitromethane solution (4 mL) of ferric chloride (648 mg, 4 mmol) was added dropwise at -78°C. After the addition was completed, the mixture was reacted for half an hour, and the temperature was naturally raised to room temperature. The mixture was diluted with dichloromethane and washed with water. The organic layer was dried over anhydrous sodium sulfate, the solvent was evaporated under reduced pressure, and then separated and purified by silica gel column chromatography. The eluent was dichloromethane-petroleum ether (v 1 :v 2=1:1) to give compound (II) (86 mg, 56%). 1 H NMR (400 MHz, CDCl 3 ): δ (ppm) 6.64 (d, J = 4Hz, 2H), 6.48 (s, 2H), 6.35 (d, J = 4.4Hz, 2H), 2.68 (s, 6H), 2.58 (s, 6H).
[0036] Example 2
[0037] Preparation of compound ZMH-3
[0038] Under anhydrous conditions, compound (II) (50 mg, 0.065 mmol) and 4-(N,N-diphenylamino)benzaldehyde (88 mg, 0.32 mmol) were placed in a 100 mL double-necked reaction bottle, freshly dried p-toluenesulfonic acid (11 mg, 0.065 mmol) was added, and then anhydrous toluene (10 mL) was added to dissolve, and piperidine (0.2 mL) was added as a catalyst, and the mixture was heated to reflux for 4 to 6 hours. After the reaction was completed, it was cooled to room temperature, diluted with dichloromethane, washed with water, dried over anhydrous sodium sulfate, and the solvent was evaporated under reduced pressure and then separated and purified by silica gel column chromatography, and the eluent was dichloromethane-petroleum ether (v 1 :v 2 =1:1), and the small molecule donor material ZMH-3 (63 mg, 54%) was obtained. 1 H NMR (CDCl 3 , 600MHz): δ (ppm) 7.64-7.58 (m, 4H), 7.49 (d, J = 8.4Hz, 4H), 7.31-7.28 (m, 14H), 7.25-7.22 (m, 8H), 7.18 (s, 2H), 7. 15 (d, J=7.2Hz, 8H), 7.10-7.08 (m, 12H), 7.04-7.01 (m, 8H), 6.94-6.92 (m, 6H), 6.72 (d, J=4.8Hz, 2H), 6.65 (s, 2H).
[0039] Example 3
[0040] Preparation of compound ZMH-4
[0041] Under anhydrous conditions, compound (II) (50 mg, 0.065 mmol) and 9-butyl-9H-carbazole-3-carboxaldehyde ((98 mg, 0.39 mmol)) were placed in a 100 mL double-necked reaction bottle, freshly dried p-toluenesulfonic acid (13 mg, 0.074 mmol) was added, and a Dean-Stark apparatus was equipped. Then, anhydrous toluene (12 mL) was added to dissolve, and piperidine (0.2 mL) was added as a catalyst, and stirred and heated to reflux for 4 to 6 hours. After the reaction was completed, it was cooled to room temperature, the mixture was diluted with dichloromethane, washed with water, and dried over anhydrous sodium sulfate. After the solvent was evaporated under reduced pressure, it was separated and purified by silica gel column chromatography, and the eluent was dichloromethane-petroleum ether (v 1 :v 2 =1:1), and the small molecule donor material ZMH-2 (47.5 mg, 43%) was obtained. 1 H NMR (CDCl 3 , 600MHz): δ (ppm) 8.41 (s, 2H), 8.29-8.26 (m, 2H), 8.22-8.17 (m, 4H), 7.96-7.87 (m, 6H), 7.72-7.65 (m, 6H) , 7.52-7.50 (m, 2H), 7.47-7.43 (m, 6H), 7.37-7.34 (m, 4H), 7.31 (t, J=7.2Hz, 2H), 7.23 (t, J=7.8Hz, 2H), 7.1 -7.08 (m, 2H), 6.72-6.71 (m, 2H), 4.34 (t, J=7.2Hz, 4H), 4.27 (t, J=7.2Hz, 4H), 3.25 (s, 2H), 1.92-1.87 (m, 4H), 1.85-1.80 (m, 4H), 1.45-1.41 (m, 4H), 1.38-1.34 (m, 4H), 0.99 (t, J=7.8Hz, 6H), 0.93 (t, J=7.2Hz, 6H).
[0042] Example 4
[0043] Thin film-electronic absorption spectra of small molecule donor materials ZMH-3, ZMH-4 and acceptor material ITIC for solar cells
[0044] Compounds ZMH-3, ZMH-4 and ITIC were dissolved in chloroform solution and spin-coated to prepare thin films, and their electronic absorption spectra were measured.
[0045] Figure 1 This is the thin film electronic absorption spectrum of small molecule donor materials ZMH-3, ZMH-4 and acceptor material ITIC for solar cells.
[0046] Example 5
[0047] Fluorescence emission spectra of thin films blended with small molecule donor materials ZMH-3, ZMH-4 and acceptor material ITIC for solar cells
[0048] Compounds ZMH-3, ZMH-3:ITIC, ZMH-4 and ZMH-4:ITIC were dissolved in chloroform solution and spin-coated to prepare thin films, and their fluorescence emission spectra were measured.
[0049] Figure 2 The fluorescence emission spectra of the thin films of small molecule donor materials ZMH-3 and ZMH-4 for solar cells and their blends with the acceptor material ITIC.
[0050] Example 6
[0051] Preparation of organic solar cell devices
[0052] The battery device is constructed of indium tin oxide (ITO) / PEDOT:PSS / active layer / PFN / Al. ITO is an indium tin oxide conductive glass substrate layer; poly(3,4-ethylenedichlorothiophene):poly(styrene sulfonate) (PEDOT:PSS) is a hole transport layer (HTL); the active layer is a binary active layer composed of a donor ZMH-3 or ZMH-4 and an acceptor ITIC, poly[(9,9-bis(3-(N,N-dimethylamino)propylfluorene)-2,7-)-alt-2,7-(9,9-dioctylfluorene) (PFN)] is an electron transport layer (ETL); and Al is a cathode.
[0053] PEDOT:PSS was spin-coated on the ITO glass which had been ultrasonically cleaned with detergent, deionized water, acetone and isopropanol and dried in vacuo at a speed of 2500rpm / min to prepare a hole transport layer with a thickness of 35-40nm; the electron donor and the electron acceptor were prepared in the above ZMH-3:ITIC mass ratios of 1:0.4, 1:0.8, 1:1.2 and 1:1.4 to prepare an active layer chloroform solution with a concentration of 16mg / mL, and spin-coated on the hole PEDOT:PSS at room temperature in a nitrogen atmosphere. On the transport layer, the spin coating speed is 2500rpm / min, and the spin coating time is 60s to form a bulk heterojunction film; then it is treated by solvent vapor annealing (SVA), and annealed in tetrahydrofuran vapor for 40s; then PFN is dissolved in methanol solvent, and the above PFN-Br methanol solution is spin-coated on the bulk heterojunction active layer to form a PFN electron transport layer, and the spin coating speed is 3000rpm / min, and the spin coating time is 60s; finally, aluminum (Al) is deposited on the top of the PFN layer by thermal evaporation under vacuum conditions.
[0054] Example 7
[0055] PEDOT:PSS was spin-coated on the ITO glass which had been ultrasonically cleaned with detergent, deionized water, acetone and isopropanol and dried in vacuo at a speed of 2500rpm / min to prepare a hole transport layer with a thickness of 35-40nm; the electron donor and the electron acceptor were prepared in the above ZMH-4:ITIC mass ratios of 1:0.4, 1:0.8, 1:1.2 and 1:1.4 to prepare an active layer chloroform solution with a concentration of 16mg / mL, and spin-coated on the hole PEDOT:PSS at room temperature in a nitrogen atmosphere. On the transport layer, the spin coating speed is 2500rpm / min, and the spin coating time is 60s to form a bulk heterojunction film; then it is treated by solvent vapor annealing (SVA), and annealed in tetrahydrofuran vapor for 40s; then PFN is dissolved in methanol solvent, and the above PFN-Br methanol solution is spin-coated on the bulk heterojunction active layer to form a PFN electron transport layer, and the spin coating speed is 3000rpm / min, and the spin coating time is 60s; finally, aluminum (Al) is deposited on the top of the PFN layer by thermal evaporation under vacuum conditions.
[0056] Example 10
[0057] In the present invention, ZMH-3 and ZMH-4 are used as solar cell donor materials and ITIC is used as a solar cell acceptor to prepare an organic solar cell, and the binary blended active layers are ZMH-3:IDT-TC (mass ratio is 1:0.4, 1:0.8, 1:1.2, 1:1.4) and ZMH-4:ITIC (mass ratio is 1:0.4, 1:0.8, 1:1.2, 1:1.4). The photoelectric conversion efficiency of the device is tested respectively, and the results are shown in Tables 1 and 2.
[0058] Table 1 Photoelectric parameters of organic solar cells with different mass ratios of active layer ZMH-3:ITIC
[0059]
[0060] a. Photoelectric parameters under optimized conditions;
[0061] Table 2 Photoelectric parameters of organic solar cells with different mass ratios of active layer ZMH-4:ITIC
[0062]
[0063] a. Photoelectric parameters under optimized conditions.
Claims
1. A class of small molecule donor materials (ZMH-3 and ZMH-4) for double BODIPY-based organic solar cells, characterized in that: Its structural formula is shown in the figure below:
2. The method for preparing a type of double BODIPY-based organic solar cell small molecule donor material according to claim 1, characterized in that: The preparation method is as follows: BODIPY derivative (I) is catalyzed by FeCl3 to generate bis-BODIPY derivative (II), which is then subjected to Knoevenagel reaction with 4-(N,N-diphenylamino)benzaldehyde and 9-butyl-9H-carbazole-3-carboxaldehyde to obtain compounds ZMH-3 and ZMH-4. The reaction formula of the preparation process is as follows:
3. The method for preparing a class of double BODIPY-based organic solar cell small molecule donor materials ZMH-3 and ZMH-4 according to claim 2, characterized in that: The characteristic method includes the following steps: 1) Under nitrogen protection, the BODIPY monomer derivative (I) is dissolved in dry dichloromethane, and a nitromethane solution of ferric chloride is added dropwise at -78°C. After the addition is completed, the mixture is reacted for half an hour, the temperature is raised to room temperature, and the mixture is extracted with dichloromethane. The organic layer is dried over anhydrous sodium sulfate, the solvent is evaporated under reduced pressure, and then separated and purified by silica gel column chromatography, the eluent being dichloromethane-petroleum ether (v:V=1:1), to obtain a coupled bis-BODIPY compound (II); 2) Under anhydrous conditions, compound (II) was placed in a 100 mL double-necked reaction bottle with 4-(N,N-diphenylamino)benzaldehyde and 9-butyl-9H-carbazole-3-carboxaldehyde, respectively. Freshly dried p-toluenesulfonic acid was added, followed by 10 mL of anhydrous toluene for dissolution, and 0.2 mL of piperidine was added as a catalyst. The mixture was stirred and heated to reflux for 4 to 6 hours. After the reaction was completed, the mixture was cooled to room temperature, diluted with dichloromethane, washed with water, and the organic layer was dried over anhydrous sodium sulfate. The solvent was evaporated under reduced pressure and then separated and purified by silica gel column chromatography. The eluent was dichloromethane-petroleum ether (v:v=1:1), and small molecule donor materials ZMH-3 and ZMH-4 were obtained.
4. Application of small molecule donor materials ZMH-3 and ZMH-4 in organic solar cells, characterized in that: The organic solar cell device is manufactured with the structure of indium tin oxide (ITO) / polyethoxythiophene (PEDOT):polystyrene sulfonic acid (PSS) / active layer / polyfluorene derivative (PFN)-Br / Al. The active layer includes a donor material and an acceptor material, and the donor material is a small molecule donor ZMH-3 and ZMH-4.
5. The organic solar cell according to claim 4, characterized in that The donor material of the active layer is ZMH-3 or ZMH-4, and the acceptor material is ITIC.
6. The organic solar cell according to claim 4, characterized in that: The best photovoltaic performance of the battery is achieved when the binary active layer blending mass ratio is ZMH-3:ITIC=1:1.2 and ZMH-4:ITIC=1:1.2, and the photoelectric conversion efficiency can reach 12.26% and 8.23%.
Citation Information
Patent Citations
Novel organic dye sensitizer containing BODYPY type conjugate units and preparation method of sensitizer
CN106221280A
Synthesis and application of (D-A)n+1D type oligomer photovoltaic donor material based on benzodithiophene-4,8-dione
CN108250222A
Preparation and application of D-A type BODIPY micromolecular non-fullerene solar cell receptor
CN114989203A
Organic solar cell small molecule donor material and preparation method and application thereof
CN115960122A
Organic solar cell micromolecule donor material and preparation method and application thereof
CN118561884A